Occupations of and occupational therapy practice with terminally ill Chinese older adults in Singapore - Lim, Geck Hoon (Curtin University, 2023)
This thesis explored the occupations of, and occupational therapy practice with terminally ill Chinese older adults in Singapore. Through the use of a scoping review and qualitative studies which explored the topic from client, caregiver, and occupational therapists’ perspectives, this thesis contributed to the body of knowledge of occupations of terminally ill persons, raised awareness of the challenges of occupational therapy practice in family-centric populations, and explored strategies to overcome these challenges.